A composite polyurethane condom and a method for preparing the same
Patent Information
- Application Number
- CN202310629837.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-05-20
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2040-05-20
AI Technical Summary
采用物理层叠的方式进行生产,但由于天然胶乳和水性聚氨酯为两种极性的材料,在层叠时两种材料间的附着力较低,造成产品易于分层,无法满足设计要求
[0033]在本发明中,通过在两层材料中间增加一层特殊的黏合层,使得两种极性不同的材料之间能够牢固的贴合在一起,不会发生分层现象。本发明将黏合层两侧的薄膜材料黏合在一起,使得各薄膜材料能够发挥各自的材料优势。本发明的黏合层具有低模量、高黏合性、高兼容性、高回弹和高附着力,通过界桥作用将不同性质的材料结合,使得本发明的安全套在50~70℃热碱水或热水中浸泡1~10分钟,也不会有分层现象发生。在本发明中,通过例如含有氨基、磺酸基和羧基基团之间的相互协同作用,能够与例如聚氨酯或非极性材料进行反应或形成良好的粘合力,使得黏合层与其两侧的材料之间具有极强的附着力,进一步保证不会发生分层现象。
Smart Images

Figure CN116672151B_ABST
Abstract
Description
[0001] This application is a divisional application of Chinese invention patent application filed on May 20, 2020, with application number 202010430483.4 and invention title "A composite polyurethane condom and its preparation method". Technical Field
[0002] This invention belongs to the field of condom technology, specifically relating to a composite polyurethane condom and its preparation method. Background Technology
[0003] Natural latex condoms are difficult to produce with a thickness below 0.04mm due to the material properties of natural latex. Furthermore, natural latex contains various proteins, posing a safety risk to individuals with protein allergies. As people's living standards improve, consumer demand for condoms has moved beyond basic contraception; people are increasingly seeking a superior user experience. Water-based polyurethane condoms are a relatively new product on the market, but polyurethane's softness is not as good as natural rubber. To combine the characteristics of both materials and create a product with both thinness and softness that meets the needs of the general public, a physical lamination method was used. However, because natural latex and water-based polyurethane are polar materials, the adhesion between them during lamination is low, causing the product to easily delaminate and failing to meet design requirements. Summary of the Invention
[0004] The present invention aims to provide a composite polyurethane condom and its preparation method. For example, by adding a special adhesive layer between two layers of materials, the two materials with different polarities can be firmly bonded together without delamination.
[0005] To solve the above problems, the present invention is achieved through the following technical solution: The present invention provides a composite polyurethane condom, comprising at least:
[0006] First substrate layer;
[0007] An adhesive layer is formed on the first substrate layer;
[0008] A second substrate layer is formed on the adhesive layer;
[0009] The adhesive layer comprises an aliphatic sulfonic acid type waterborne polyurethane, wherein the molecular chain of the aliphatic sulfonic acid type waterborne polyurethane contains amino, sulfonic acid, and carboxyl groups, and the 100% modulus of the aliphatic sulfonic acid type waterborne polyurethane is less than or equal to 1.2 N / mm². 2 The thickness of the adhesive layer is 0.1–20 μm.
[0010] In one embodiment, the first substrate layer includes any one of a natural latex film, a synthetic rubber film, a polyurethane film, and a polyisoprene film.
[0011] In one embodiment, the second substrate layer comprises any one of a natural latex film, a synthetic rubber film, a polyurethane film, and a polyisoprene film.
[0012] In one embodiment, the aliphatic sulfonic acid-based waterborne polyurethane comprises polyether / polyester polyol, aliphatic isocyanate, crosslinking agent, small molecule chain extender, and hydrophilic chain extender.
[0013] In one embodiment, the polyether / polyester polyol has a molecular weight of 400-6000, and the polyether / polyester polyol includes any one or more combinations of polypropylene glycol, polytetramethylene ether glycol, polypentyl adipate, polybutylene adipate, polyhexanediol adipate, polycaprolactone, and polycarbonate.
[0014] In one embodiment, the aliphatic isocyanate includes one or more combinations of aliphatic isocyanates such as hexamethylene diisocyanate (HDI), isoflurane diisocyanate (IPDI), and dicyclohexylmethane-4,4'-diisocyanate (HMDI).
[0015] In one embodiment, the crosslinking agent includes any one or more combinations of trimethylolpropane, silanes, neopentyl glycol, and castor oil.
[0016] In one embodiment, the hydrophilic chain extender is any one or a combination of two of sodium ethylenediamine ethanesulfonate and dimethylolpropionic acid (DMPA).
[0017] In one embodiment, the number-average molecular weight of the adhesive layer is 20,000-60,000 g / mol.
[0018] In one embodiment, the composite polyurethane condom further includes:
[0019] A second adhesive layer is formed on the second substrate layer;
[0020] A third substrate layer is formed on the second adhesive layer.
[0021] In one embodiment, the elongation at break of the adhesive layer is greater than or equal to 500%.
[0022] In one embodiment, the thickness of the condom is 0.01 to 0.068 mm.
[0023] In one embodiment, the condom has 3 to 6 layers.
[0024] In one embodiment, the molecular chain of the aliphatic sulfonic acid type waterborne polyurethane further includes silane groups and / or hydroxyl groups.
[0025] Another object of the present invention is to provide a method for preparing a composite polyurethane condom, comprising at least the following steps:
[0026] Provide a mold;
[0027] A first substrate layer is formed on the mold;
[0028] An adhesive layer is formed on the first substrate layer;
[0029] A second substrate layer is formed on the adhesive layer;
[0030] Remove the mold to obtain the composite polyurethane condom;
[0031] The adhesive layer comprises an aliphatic sulfonic acid type waterborne polyurethane, wherein the molecular chain of the aliphatic sulfonic acid type waterborne polyurethane contains amino, sulfonic acid, and carboxyl groups, and the 100% modulus of the aliphatic sulfonic acid type waterborne polyurethane is less than or equal to 1.2 N / mm². 2 The thickness of the adhesive layer is 0.1 to 20 μm.
[0032] In one embodiment, the mold is removed by using release water containing a release agent.
[0033] In this invention, a special adhesive layer is added between two layers of materials, allowing two materials with different polarities to adhere firmly together without delamination. This invention bonds the film materials on both sides of the adhesive layer together, allowing each film material to leverage its own advantages. The adhesive layer of this invention has low modulus, high adhesion, high compatibility, high resilience, and high adhesion. Through a bridging effect, it combines materials with different properties, ensuring that the condom of this invention will not delaminate even after immersion in hot alkaline or hot water at 50–70°C for 1–10 minutes. In this invention, through the synergistic effect of, for example, amino, sulfonic acid, and carboxyl groups, it can react with, for example, polyurethane or non-polar materials to form good adhesion, resulting in extremely strong adhesion between the adhesive layer and the materials on both sides, further ensuring that delamination does not occur. Attached Figure Description
[0034] Figure 1 : A schematic diagram of a composite polyurethane condom with a 3-layer structure in one embodiment of the present invention;
[0035] Figure 2 : A schematic diagram of the method flow in one embodiment of the present invention;
[0036] Figure 3: A schematic diagram of a composite polyurethane condom with a 5-layer structure in one embodiment of the present invention.
[0037] Symbol Explanation
[0038] 101 First substrate layer
[0039] 102 Adhesive Layer
[0040] 103 Second substrate layer
[0041] 104 Second adhesive layer
[0042] 105 Third substrate layer Detailed Implementation
[0043] The present invention will be further illustrated below through several specific embodiments. However, it should be noted that the specific material ratios, process conditions, and results described in the embodiments of the present invention are only for illustrative purposes and should not be used to limit the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention. Note that unless otherwise specified, "%" in this description refers to "parts by mass".
[0044] In this invention, it should be noted that the terms "center," "upper," "lower," "left," "right," "vertical," "horizontal," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this application. Furthermore, the terms "first" and "second" are used only for descriptive and distinguishing purposes and should not be construed as indicating or implying relative importance.
[0045] This invention provides a composite polyurethane condom and its preparation method. By adding a special adhesive layer between two layers of materials, for example, two materials with different polarities can be firmly bonded together. This allows the condom of this invention to remain in place even after being soaked in hot alkaline water or hot water at 50-70°C for 1-10 minutes without delamination.
[0046] Please see Figure 2 The diagram below illustrates a process for preparing a composite polyurethane condom according to an embodiment of the present invention, comprising at least the following steps:
[0047] S1. Provide a mold;
[0048] S2. A first substrate layer is formed on the mold;
[0049] S3. An adhesive layer is formed on the first substrate layer;
[0050] S4. A second substrate layer is formed on the adhesive layer;
[0051] S5. Remove the mold to obtain the composite polyurethane condom;
[0052] The adhesive layer comprises an aliphatic sulfonic acid type waterborne polyurethane, wherein the molecular chain of the aliphatic sulfonic acid type waterborne polyurethane contains amino, sulfonic acid, and carboxyl groups, and the 100% modulus of the aliphatic sulfonic acid type waterborne polyurethane is less than or equal to 1.2 N / mm². 2 The thickness of the adhesive layer is 0.1–20 μm.
[0053] Specifically, in step S1, the mold is, for example, a glass or other material condom mold.
[0054] Specifically, in step S2, for example, the surface of the mold is heated to 30-40°C, and then the mold is immersed in an impregnation solution containing the material of the first substrate layer 101 for an immersion time of, for example, 35-60 seconds. After immersion, the mold is removed and dried at, for example, 90-110°C. The immersion can be repeated. The material of the first substrate layer 101 is, for example, any one of natural latex film, synthetic rubber film, polyurethane film, and polyisoprene film.
[0055] Specifically, in step S3, the mold on which the first substrate layer 101 is formed is immersed in a liquid containing the adhesive layer 102 material for an immersion time of, for example, 35 to 60 seconds. After immersion, it is removed and dried at, for example, 80 to 120°C. The immersion can be repeated to form the adhesive layer 102. The material of the adhesive layer 102 includes, for example, aliphatic sulfonic acid-based waterborne polyurethane. Specifically, the thickness of the adhesive layer 102 is, for example, 0.1 to 10 μm.
[0056] Specifically, in step S4, the mold with the adhesive layer 102 is immersed in a liquid containing the material of the second substrate layer 103 for an immersion time of, for example, 35 to 60 seconds. After immersion, it is removed and dried at, for example, 100 to 140°C. The immersion process can be repeated to form the second substrate layer 103. The material of the first substrate layer 101 is, for example, any one of natural latex film, synthetic rubber film, polyurethane film, and polyisoprene film. The materials of the first substrate layer 101 and the second substrate layer 103 may have different polarities, or they may have the same polarity. The adhesive layer 102 of this invention combines materials with different properties through a boundary bridging effect, enabling, for example, two materials with different polarities to be firmly bonded together.
[0057] Specifically, in step S5, the polyurethane condom is swollen using hot alkaline water, and then demolded using water jetting (e.g., adding a release agent to the demolding water) to remove the mold. It is then dried, for example, in a dryer, to obtain the composite polyurethane condom. The composite polyurethane condom may have four, five, or six layers, among other layers. The adhesive layer 102 serves as one or two intermediate layers, and other material films are laminated to both sides of each adhesive layer.
[0058] Please see Figure 1 As shown, one embodiment of the present invention also provides a composite polyurethane condom, the condom having a thickness of 0.01–0.068 mm. The condom has, for example, 3–6 layers. Specifically, it includes at least: a first substrate layer 101, an adhesive layer 102, and a second substrate layer 103. The adhesive layer 102 is formed on the first substrate layer 101. The second substrate layer 103 is formed on the adhesive layer 102. The adhesive layer 102, for example, comprises an aliphatic sulfonic acid type waterborne polyurethane, the molecular chain of which contains unsaturated double bonds, amino groups, sulfonic acid groups, and carboxyl groups, capable of chemically reacting with the first substrate layer 101 and the second substrate layer 103 to form, for example, chemical bonds. In another embodiment, the molecular chain of the aliphatic sulfonic acid type waterborne polyurethane further includes, for example, silane groups and / or hydroxyl groups. The 100% modulus of the aliphatic sulfonic acid type waterborne polyurethane is less than or equal to 1.2 N / mm². 2 The adhesive layer has a thickness of 0.1–20 μm and an elongation at break of, for example, greater than or equal to 500%. The first substrate layer 101 includes, for example, any one of a natural latex film, a synthetic rubber film, a polyurethane film, and a polyisoprene film. The second substrate layer 103 includes, for example, any one of a natural latex film, a synthetic rubber film, a polyurethane film, and a polyisoprene film. The polarities of the materials of the first substrate layer 101 and the second substrate layer 103 are, for example, different. The adhesive layer 102 of the present invention is, for example, an aliphatic polyester-type waterborne polyurethane material, synthesized using polyester polyols, which has extremely strong adhesion to both polar and non-polar materials, while also possessing flexibility and high elongation, with a 100% modulus less than or equal to 1.2 N / mm². 2The elongation at break is greater than or equal to 500%. In one embodiment, the aliphatic sulfonic acid-type waterborne polyurethane comprises a polyether / polyester polyol, an aliphatic isocyanate, a crosslinking agent, a small molecule chain extender, and a hydrophilic chain extender. In one embodiment, the molecular weight of the polyether / polyester polyol is 400-6000, and the polyether / polyester polyol comprises any one or more combinations of polypropylene glycol, polytetramethylene ether glycol, polypentyl adipate, poly1,4-butylene adipate, poly1,6-hexane adipate, polycaprolactone, and polycarbonate. In one embodiment, the aliphatic isocyanate comprises one or more combinations of hexamethylene diisocyanate (HDI), isoflurane diisocyanate (IPDI), dicyclohexylmethane-4,4'-diisocyanate (HMDI), etc. In one embodiment, the crosslinking agent comprises any one or more combinations of trimethylolpropane, silanes, neopentyl glycol, and castor oil. In one embodiment, the hydrophilic chain extender is any one or a combination of two of sodium ethylenediamine ethanesulfonate and dimethylolpropionic acid (DMPA). This invention, for example, adds an adhesive layer between two layers of natural latex and waterborne polyurethane during lamination, which is an effective method to overcome the deficiencies of the prior art. For example, the number average molecular weight of the adhesive layer is 20,000-60,000 g / mol, which is beneficial for promoting strong adhesion, for example, between the first substrate layer 101 and the adhesive layer 102, and between the second substrate layer 103 and the adhesive layer 102.
[0059] Please see Figure 3 As shown, in some embodiments, the composite polyurethane condom further includes, for example, a second adhesive layer 104 and a third substrate layer 105. The second adhesive layer 104 is formed on the second substrate layer 103, and the third substrate layer 105 is formed on the second adhesive layer 102. The polarity of the third substrate layer 105 and the second substrate layer 103 may be the same or different. The third substrate layer 105 is, for example, any one of a natural latex film, a synthetic rubber film, a polyurethane film, and a polyisoprene film.
[0060] Please see Figure 1 As shown, in some embodiments, the first substrate layer 101 is, for example, a natural latex film or a synthetic rubber film, and the adhesive layer 102 is, for example, an aliphatic sulfonic acid-type waterborne polyurethane containing unsaturated double bonds, amino groups, and carboxyl groups on its molecular chain, wherein the 100% modulus of the aliphatic sulfonic acid-type waterborne polyurethane is less than or equal to 1.2 N / mm². 2The adhesive layer has a thickness of 0.1–20 μm, and the second substrate layer 103 is made of, for example, a polyurethane film. In other embodiments, the first substrate layer 101 is, for example, a natural latex film or a synthetic rubber film, and the adhesive layer 102 is, for example, an aliphatic sulfonic acid-type waterborne polyurethane containing unsaturated double bonds, amino groups, and carboxyl groups on its molecular chain, wherein the 100% modulus of the aliphatic sulfonic acid-type waterborne polyurethane is less than or equal to 1.2 N / mm². 2 The adhesive layer has a thickness of 0.1–20 μm, and the material of the second substrate layer 103 is, for example, a polyisoprene (PI) film. In some other embodiments, the first substrate layer 101 is a polyisoprene (PI) film, such as an aqueous polyurethane film, and the adhesive layer 102 is, for example, an aliphatic sulfonic acid type aqueous polyurethane containing unsaturated double bonds, amino groups, and carboxyl groups on its molecular chain, wherein the 100% modulus of the aliphatic sulfonic acid type aqueous polyurethane is less than or equal to 1.2 N / mm². 2 The thickness of the adhesive layer is 0.1 to 20 μm, and the material of the second substrate layer 103 is, for example, a polyisoprene (PI) film.
[0061] The following examples illustrate the present invention in detail.
[0062] Referring to the data in Table 1, in one embodiment, for example, a glass mold or other material condom mold is cleaned, the mold surface is heated to 30-40°C, and the mold is immersed in a latex liquid, such as a latex liquid containing natural latex or synthetic rubber, for an immersion time of 35-60 seconds. After immersion, the mold is removed and dried at, for example, 90-110°C. This process can be repeated to obtain latex layer A. Next, the mold with the latex layer is immersed in a liquid containing the adhesive layer A material for an immersion time of 35-60 seconds. After immersion, the mold is removed and dried at, for example, 80-120°C. This process can be repeated to form adhesive layer A. The material of adhesive layer A includes, for example, an aliphatic sulfonic acid type waterborne polyurethane, specifically, an aliphatic polyester type waterborne polyurethane. The thickness of adhesive layer A is controlled, for example, to be 0.1-10 μm. Then, the mold with the adhesive layer A formed thereon is immersed in a liquid containing waterborne polyurethane for, for example, 35 to 60 seconds. After immersion, it is removed and dried at, for example, 100 to 140°C. The immersion can be repeated to form the waterborne polyurethane layer A. An edge-rolling process is then performed, followed by drying at 120 to 140°C. The mold is then swelled using hot alkaline water, demolded by water rinsing, with a release agent added to the demolding water, and finally dried in a dryer to obtain a composite polyurethane condom A. In this embodiment, one side is latex material and the other side is waterborne polyurethane material, which are two materials with different polarities.
[0063] Please refer to the data in Table 1. In another embodiment, both sides of the adhesive layer B in this embodiment are adhered with latex material, which is a material of the same polarity. For example, clean the glass mold or other condom mold, heat the surface of the mold to 30-40°C, and immerse the mold in a latex liquid, such as a latex liquid containing natural latex or synthetic rubber, for an immersion time of 35-60 seconds. After immersion, remove the mold and dry it at, for example, 90-110°C. The immersion can be repeated to obtain latex layer B. Next, immerse the mold with the latex layer formed in a liquid containing the adhesive layer material for an immersion time of 35-60 seconds. After immersion, remove the mold and dry it at, for example, 80-100°C. The immersion can be repeated to form adhesive layer B. The material of adhesive layer B includes, for example, aliphatic sulfonic acid type waterborne polyurethane, specifically, aliphatic polyester type waterborne polyurethane. The thickness of adhesive layer B is controlled, for example, 0.1-10 μm. Then, the mold with the adhesive layer B formed thereon is immersed in a liquid containing latex liquid B1 for, for example, 35 to 60 seconds. After immersion, it is removed and dried at, for example, 90 to 110°C. The immersion can be repeated to form latex liquid B1. The mold is then rolled at the edges and dried at 100 to 120°C. It is then swollen using hot alkaline water, demolded by water rinsing, with a release agent added to the demolding water, and finally dried in a dryer to obtain the composite polyurethane condom B.
[0064] Please refer to the data in Table 1. In another embodiment, both sides of the adhesive layer C in this embodiment are adhered with waterborne polyurethane material, which is a material with the same polarity. For example, clean the glass mold or other condom mold, heat the surface of the mold to 30-40°C, and immerse the mold in liquid C1 containing waterborne polyurethane for, for example, 35-60 seconds. After immersion, remove it and dry it at, for example, 90-110°C. This process can be repeated to obtain the waterborne polyurethane layer C1. Next, immerse the mold with the waterborne polyurethane layer C1 formed in it in liquid containing the adhesive layer C material for, for example, 35-60 seconds. After immersion, remove it and dry it at, for example, 80-100°C. This process can be repeated to form the adhesive layer C. The material of the adhesive layer C includes, for example, an aliphatic sulfonic acid type waterborne polyurethane, specifically, for example, an aliphatic polyester type waterborne polyurethane. The thickness of the adhesive layer C is controlled, for example, to be 0.1-10 μm. Then, the mold with the adhesive layer C formed is immersed in a liquid C2 containing waterborne polyurethane for, for example, 35 to 60 seconds. After immersion, it is removed and dried at, for example, 100 to 120°C. The immersion can be repeated to form the waterborne polyurethane layer C2. The edges are then rolled and dried at 120 to 140°C. The mold is then swollen using hot alkaline water, demolded by water rinsing, with a release agent added to the demolding water, and finally dried in a dryer to obtain the composite polyurethane condom C.
[0065] Please refer to the data in Table 1. In one embodiment, the adhesive layer C in this embodiment has latex material adhered to one side and polyisoprene (PI) adhered to the other side, which are materials with different polarities. For example, clean the glass mold or other condom mold made of other materials, heat the surface of the mold to 30-40°C, and immerse the mold in a latex liquid, such as a latex liquid containing natural latex or synthetic rubber, for an immersion time of 35-60 seconds. After immersion, remove the mold and dry it at, for example, 90-110°C. The immersion can be repeated to obtain the latex layer D. Next, immerse the mold with the latex layer formed in a liquid containing the adhesive layer D material for an immersion time of 35-60 seconds. After immersion, remove the mold and dry it at, for example, 80-120°C. The immersion can be repeated to form the adhesive layer D. The adhesive layer D is made of, for example, an aliphatic sulfonic acid-based waterborne polyurethane, specifically, an aliphatic polyester-based waterborne polyurethane. The thickness of the adhesive layer D is controlled, for example, to be 0.1–10 μm. Then, the mold with the adhesive layer D formed is immersed in a liquid containing polyisoprene (PI) for, for example, 35–60 seconds. After immersion, it is removed and dried at, for example, 100–140°C. This process can be repeated to form the polyisoprene layer D. The edges are then rolled, dried at 120–140°C, swollen using hot alkaline water, and demolded by water rinsing. A release agent is added to the demolding water, and the product is then dried in a dryer to obtain the composite polyurethane condom D.
[0066] The composite polyurethane condoms obtained from the embodiments and comparative examples listed above were subjected to relevant performance tests, and the test results are shown in Table 1.
[0067] Table 1. Performance Test Table
[0068]
[0069] As can be seen from the data in Table 1 and the various embodiments, by adding a special adhesive layer between the two materials, the two materials with different polarities can be firmly bonded together. This ensures that the condom of the present invention will not delaminate even after being immersed in hot alkaline water or hot water at 50-70°C for 1-10 minutes. When materials of different polarities are adhered to both sides of the adhesive layer, the advantages of the different polarities can be maximized, resulting in a composite polyurethane condom with low modulus, high adhesion, high compatibility, high resilience, and high bonding strength. For example, after immersion in hot alkaline water or hot water at 50-70°C for 1-10 minutes, there is no delamination, and the elongation at break can reach, for example, 700% and 550%.
[0070] In summary, this invention adds a special adhesive layer between two layers of material, enabling two materials with different polarities to adhere firmly together without delamination. This invention bonds the film materials on both sides of the adhesive layer together, allowing each film material to leverage its respective advantages. The adhesive layer of this invention has low modulus, high adhesion, high compatibility, high resilience, and high adhesion. Through a bridging effect, it combines materials with different properties, ensuring that the condom of this invention will not delaminate even after immersion in hot alkaline or hot water at 50–70°C for 1–10 minutes. In this invention, through the synergistic effect of, for example, unsaturated double bonds, amino groups, sulfonic acid groups, and carboxyl groups, it can react with, for example, polyurethane or vinyl groups, resulting in extremely strong adhesion between the adhesive layer and the materials on both sides, further ensuring that delamination does not occur.
[0071] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any form or substance. It should be noted that those skilled in the art can make various improvements and additions without departing from the method of the present invention, and these improvements and additions should also be considered within the scope of protection of the present invention. Any modifications, alterations, and equivalent changes made by those skilled in the art based on the above-disclosed technical content without departing from the spirit and scope of the present invention are equivalent embodiments of the present invention. Furthermore, any modifications, alterations, and evolutions made to the above embodiments based on the essential technology of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A composite polyurethane condom, characterized in that, At least including: First substrate layer; An adhesive layer is formed on the first substrate layer; A second substrate layer is formed on the adhesive layer; The adhesive layer comprises an aliphatic sulfonic acid type waterborne polyurethane, wherein the molecular chain of the aliphatic sulfonic acid type waterborne polyurethane contains unsaturated double bonds, amino groups, sulfonic acid groups and carboxyl groups, the 100% modulus of the aliphatic sulfonic acid type waterborne polyurethane is less than or equal to 1.2 N / mm2, and the thickness of the adhesive layer is 0.1 to 10 μm. The number-average molecular weight of the adhesive layer is 20,000-60,000 g / mol; The elongation at break of the adhesive layer is 500%~700%; The first substrate layer and the second substrate layer are made of materials with different polarities, and are selected from one of the following combinations: The first substrate layer is a natural latex film or a synthetic rubber film, and the second substrate layer is a polyurethane film. The first substrate layer is a natural latex film or a synthetic rubber film, and the material of the second substrate layer is a polyisoprene (PI) film, or The first substrate layer is an aqueous polyurethane film, and the second substrate layer is a polyisoprene (PI) film.
2. The composite polyurethane condom according to claim 1, characterized in that, The aliphatic sulfonic acid type waterborne polyurethane includes polyether / polyester polyol, aliphatic isocyanate, crosslinking agent, small molecule chain extender and hydrophilic chain extender.
3. The composite polyurethane condom according to claim 2, characterized in that, The molecular weight of the polyether / polyester polyol is 400-6000, and the polyether / polyester polyol includes any one or more combinations of polypropylene glycol, polytetramethylene ether glycol, polypentyl adipate, 1,4-butyl adipate, 1,6-hexanediol adipate, polycaprolactone, and polycarbonate.
4. The composite polyurethane condom according to claim 2, characterized in that, The aliphatic isocyanate includes one or more combinations of hexamethylene diisocyanate, isoflurane diisocyanate, and dicyclohexylmethane-4,4'-diisocyanate.
5. The composite polyurethane condom according to claim 2, characterized in that, The crosslinking agent includes any one or more combinations of trimethylolpropane, silanes, neopentyl glycol, and castor oil.
6. The composite polyurethane condom according to claim 2, characterized in that, The hydrophilic chain extender is any one or a combination of two of sodium ethylenediamine ethanesulfonate and dimethylolpropionic acid.
Citation Information
Patent Citations
Full-synthetic or composite water-based polyurethane condom
CN103692733A
Multilayer condom containing modified polyurethane raw material and preparation method of multilayer condom
CN111072902A